Partisipasi Masyarakat dalam Pengelolaan Sampah di Kota Gorontalo - Mohammad Bayu Irawan; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
City growth that is not balanced with the fulfillment of community needs has the potential to reduce environmental quality, especially in waste management. This study aims to analyze community participation in waste management in Gorontalo City. The method used is descriptive qualitative, with data collection through interviews, observation, and documentation. The results showed that community participation in waste management is still low, as seen from the large amount of littering and lack of knowledge about waste utilization. However, there are positive developments in Kelurahan Dulomo Utara, where people are starting to realize the importance of separating waste and managing waste into useful products. The study also identified challenges, including a lack of facilities and socialization from the government. Hopefully, increased community participation and government support can create a sustainable solution for waste management in Gorontalo City.